2006
DOI: 10.1103/physrevb.74.064403
|View full text |Cite
|
Sign up to set email alerts
|

Barkhausen statistics from a single domain wall in thin films studied with ballistic Hall magnetometry

Abstract: The movement of a micron-size section of an individual domain wall in a uniaxial garnet film was studied using ballistic Hall micromagnetometry. The wall propagated in characteristic Barkhausen jumps, with the distribution in jump size S, following the power-law relation, D͑S͒ ϰ S −. In addition to reporting on the suitability of employing this alternative technique, we discuss the measurements taken of the scaling exponent , for a single domain wall in a two-dimensional sample with magnetization perpendicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 39 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…Since the spin valve 13) by Fe 3 O 4 has a complex structure, essential understanding of the magnetization process is not sufficient. In this paper, our aim is to build a theory of magnetization process for spin valve of Fe 3 O 4 as a ferrimagnetic material and derive the magnetic hysteresis loop with various parameter by the computer simulation using retarded trace method.…”
Section: Introductionmentioning
confidence: 99%
“…Since the spin valve 13) by Fe 3 O 4 has a complex structure, essential understanding of the magnetization process is not sufficient. In this paper, our aim is to build a theory of magnetization process for spin valve of Fe 3 O 4 as a ferrimagnetic material and derive the magnetic hysteresis loop with various parameter by the computer simulation using retarded trace method.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these systems exhibit avalanches which have power law size distributions. These include Barkhausen noise in ferromagnets [4][5][6][7][8], fluid imbibition into porous media, flux-line depinning [3,[9][10][11][12][13], and martensitic transformations [14,15], to name a few. In the first three of these systems, avalanches are the result of the jerky motion of an interface (domain wall, fluid front, flux line) in a disordered environment, and can be described by the same family of front-propagation models.…”
Section: Introductionmentioning
confidence: 99%
“…All experiments presented here are carried out using such notches with a triangular geometry. In soft-magnetic nanowires with submicron width and thicknesses of some 10 [13,17]. Transitions between these metastable states are possible, e.g., by depinning a DW from a notch [13] or interaction with spin-polarized currents [18].…”
Section: Resultsmentioning
confidence: 99%
“…Our Hall sensors allow to identify the presence of an individual DW via detecting its stray field in a region of about 1 mm 2 [8]. It has been demonstrated that the technique is sufficiently sensitive to track the motion of magnetization in the Peierls potential with subatomic resolution [9] and to measure the Barkhausen statistics of a single DW in garnet films [10]. The micromagnetic configuration of the ferromagnetic specimens is not affected by the Hall measurements due to the low susceptibility of the semiconductor heterostructure.…”
Section: Introductionmentioning
confidence: 99%